Physicochemical and Medicinal Properties of Tualang, Gelam and Kelulut Honeys: A Comprehensive Review - Datu Agasi Mohd Kamal; Siti Fatimah Ibrahim; Haziq Kamal; Mohd Izhar Ariff Mohd Kashim; Mohd Helmy Mokhtar (MDPI, 2021)
Tualang, Gelam and Kelulut honeys are tropical rainforest honeys reported to have various medicinal properties. Studies related to the medicinal properties and physicochemical characteristics of these honeys are growing extensively and receiving increased attention. This review incorporated and analysed the findings on the biological and physicochemical properties of these honeys. Tualang, Gelam and Kelulut honeys were found to possess a wide variety of biological effects attributed to their physicochemical characteristics. Findings revealed that these honeys have anti-diabetic, anti-obesity, anti-cancer, anti-oxidative, anti-microbial, anti-inflammatory and wound-healing properties and effects on the cardiovascular system, nervous system and reproductive system. The physicochemical properties of these honeys were compared and discussed and results showed that they have highquality contents and excellent antioxidant sources.